Comparison of the Mean Post-Operative Pain Score with Ultrasound Guided Transversus Abdominis Plane (TAP) Block and Wound Infiltration with Local an Aesthetic Agent in Abdominal Surgeries - Sadique, Abubakar; Sharif, Asjad; Gulrez, Amna (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To compare the mean post-operative pain score with ultrasound-guided transversus abdominis plane block and wound infiltration with local anaesthetic agents in abdominal surgeries.Study design: Comparative prospective studyPlace and Duration of Study: Department of Anaesthesia, Intensive Care and Pain Management, Combined Military Hospital, Bahawalpur Pakistan, from Oct 2018 to Apr 2019.Methodology: Sixty patients undergoing abdominal surgery aged 18-60 years were included. The patients in Group-A received transverses abdominis plane block with 20 ml of 0.25% Bupivacaine bilaterally, while those in Group-B received 20 ml of 0.25% Bupivacaine as local wound infiltration. Each patient was followed till 6 hours post-operatively.Results: Out of 60 patients, 35(58.33%) were male, and 25(41.67%) were females. In our study, the Visual analogue score was 1.63±0.85 in Group-A (ultrasound-guided TAP block) compared with 4.47±1.07 in patients with Group-B (wound infiltration with a local anaesthetic agent) with a p-value of 0.001, which was statistically significant.Conclusion: The study concluded that the mean pain score in patients with ultrasound-guided Transversus abdominis plane block is less compared to wound infiltration with local anaesthetic agents in abdominal surgeries.